2000
DOI: 10.1017/s0048577200980983
|View full text |Cite
|
Sign up to set email alerts
|

Error monitoring during reward and avoidance learning in high- and low-socialized individuals

Abstract: The error-related negativity (ERN) is a response-locked brain potential generated when individuals make mistakes during simple decision-making tasks. In the present study, we examined ERN under conditions of reward and punishment, among participants who scored extremely low or high on the socialization scale of the California Psychological Inventory (CPI). Participants completed a forced-choice task, and were rewarded for correct responses in half the trials, and punished for incorrect responses in the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 0 publications
9
92
2
1
Order By: Relevance
“…In the current study, F-ERN amplitude was not associated with symptoms of antisocial personality disorder. However, reduced R-ERNs have been reported in low-socialized individuals compared to high-socialized individuals (Dikman and Allen, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, F-ERN amplitude was not associated with symptoms of antisocial personality disorder. However, reduced R-ERNs have been reported in low-socialized individuals compared to high-socialized individuals (Dikman and Allen, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…a Stroop or flanker task), the participant does not necessarily require feedback to know that he has made a mistake. In this case, an ERN occurs about 50-150ms after the erroneous response and is called a response-locked error-related negativity (R-ERN) [for example: (Dikman and Allen, 2000;Falkenstein et al, 2001;Hajcak and Simons, 2002)]. The R-ERN reflects low-level error recognition, as it is present even when individuals are not consciously aware of their errors (Nieuwenhuis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the performance of individuals with PP in certain learning paradigms is modulated by reward but not by punishment . Additionally, it has been reported that low socialized individuals (a trait closely related to PP) show diminished rERNs under conditions of punishment but not reward (Dikman & Allen, 2000). With regard to the current task, individuals with PP might have learned based on reward cues, but not on punishment cues, which leads to diminished learning performance as only some of the trials (the rewarded but not the punished) are used to adapt behaviour.…”
Section: Electrophysiological Findingsmentioning
confidence: 94%
“…Until now, most studies either focused on individuals with behavioural patterns related to PP (Dikman & Allen, 2000 ;Hall et al 2007) or investigated aspects of error monitoring unrelated to learning (Munro et al 2007 ;Brazil et al 2009). An investigation of reward and avoidance learning in low socialized individuals (a concept related to PP ; Kosson & Newman, 1989) has shown diminished rERN amplitudes only in the punishment condition (Dikman & Allen, 2000). Another study demonstrated reduced rERN amplitudes in healthy individuals scoring high on externalizing psychopathology, a factor comparable to the behavioural deficit cluster in individuals with PP (Hall et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Error trials have been reported to be associated with faster responses than correct trials in a simple discrimination task (Dikman and Allen, 2000). The faster responses on error trials may be caused by impulsive responding.…”
Section: Faculty Of Design Kyushu Universitymentioning
confidence: 99%